Priority Analysis of Community Preparedness for Megathrust Earthquakes Using Analytic Hierarchy Process (AHP): A Case Study of Warungboto Village, Yogyakarta - Bawono, Adi Setiabudi; Nur Huda, Muhamad (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2026)
The Special Region of Yogyakarta is highly vulnerable to megathrust earthquakes due to its proximity to an active subduction zone, posing significant risks to communities. While structural mitigation is important, community preparedness is critical to disaster risk reduction. This study aims to identify and prioritise factors influencing preparedness using the Analytic Hierarchy Process (AHP), with a case study in Warungboto Village. Data were collected from 30 respondents using pairwise-comparison questionnaires. Four main criteria were evaluated: Public Education and Awareness, Infrastructure Resilience, Emergency Response Management, and Social and Psychological Factors. The results show that Public Education and Awareness is the most influential factor (35.81%), followed by Infrastructure Resilience (24.10%), Emergency Response Management (20.20%), and Social and Psychological Factors (20.00%). Key sub-criteria include disaster drills, education programs, and awareness levels. All Consistency Ratio (CR) values are below 0.1, indicating reliable results. These findings highlight the importance of education-based strategies in enhancing community preparedness.